The affective origins of the Industrial Revolution. (2019) - Huntsinger, Jeffrey R.; Raoul, Akila
Abstract: We suggest in this commentary an emotional origin of the Industrial Revolution. Specifically, increased living standards directly preceding the Industrial Revolution produced increased happiness and subjective well-being that, in turn, fueled the explosion of innovation and economic growth experienced in industrial England.